A Network Analysis of Online News Portal Discourse on the Change of Coach of the 2025 Indonesian National Football Team - Revina, Angelia; Nugroho, Catur (Yayasan Ilomata, 2025)
Fan​ often show fanatical attitudes, which can lead to verbal aggression and increase the potential for the spread of various negative opinions. Many online news portals report diversity opinion One example of the diversity of opinion in football concerns the policies implemented by the PSSI in early 2025, particularly regarding the replacement of the Indonesian national team coach. This will use approach method mixed, but will more focused on approach qualitative with use method Analysis Discourse Network (DNA). Online news portal, or The actors involved can certainly play a significant role in disseminating discourse. Therefore, this study aims to understand how discourse networks and actor networks are formed. The research method used involves utilizing Discourse Network Analyzer (DNA) and Visone by analyzing 55 articles. online news. The results showed that there were 292 statements, and 30 organizations were involved, with 55 individual actors participating. Furthermore, it should be noted that in the topic of changing the coach of the Indonesian national football team, there were pro and con groups. The discourse of support for the new coach had the highest centrality, namely 11.066%. Furthermore, Hadrian Irfani, Deputy Chairman of Commission X of the House of Representatives, was the actor with the highest contribution in this topic, with score centrality degrees by 2.869%.